Effect of Indonesian medicinal plants essential oils on Streptococcus mutansbiofilm - Triana Hertiani; Sylvia Utami Tanjung Pratiwi; Irami Duma Kencana Irianto; Dian Adityaningrum; Budi Pranoto (Indonesian Journal of Pharmacy, 2011)
Essential  oil’s  component  such  as  menthol  and  eucalyptol  were  already used as dental plaque inhibitors. In searching of potential dental plaque inhibitor from natural products, a study to explore the potency of essential oils extracted from  several  Indonesian  medicinal  plants  against  planktonic  growth  and  biofilm adherence  of  S.  mutans was  performed.  A  total  of  14  essential  oils  from  some selected Indonesian medicinal plants were extractedby steam-hydro distillation. Antibacterial assay was performed against S. mutansby micro dilution technique on  nutrient  broth  media.  Biofilm  formation  inhibition  assay  was  conducted  on  a flexible  U-bottom  96-wells  PVC  micro  plate  by  using BHI  enriched  with  sucrose 2%  at  36.6  °C  for  18-24  h.  After  staining  with  1%  crystal  violet,  the  optical density  was  read  at  595  nm.  A  mouthwash  commercial  product  containing essential  oil  component  was  used  as  a  positive  control.  Result  showed  that  the essential oils of  C. sintoc exhibited the highest biofilm formation inhibition (IC50 =  0.005%),  and  Z.  officinale showed  the  highest  biofilm  degradation  with  EC50 value  of  0.013%.  Both  were  active  against  bacterial planktonic  growth  but  C. sintocshowed lower MIC90 value (0.6%) in comparison to Z. officinale(0.06%). Meantime,  C.  citratus was  showed  promising  antibacterial  and  antibiofilmactivities with MIC90 value of 0.06%, MBC 0.6%, IC50 0.008% and EC50 0.026%. It is concluded that the essential oils of C. citratus, Z. officinaleand C. sintocare potential to be developed as dental plaque inhibitors.Key words: essential oils, antibacterial, biofilm, Streptococcus mutans